(untitled) (Bangladesh Journal of Medical Science, 2018)
Background: Increase of SIRT1 expression inhibit the increase of activated Caspase 3 expression in acute phase of traumatic brain injury (TBI). However, the SIRT1 expression on rat spinal cord in acute phase after peripheral nerve injury was unknown. Objective: To reveal SIRT1and activated Caspase 3 expression on rat spinal cord in acute phase after sciatic nerve injury and to reveal the correlation between SIRT1 and activated Caspase 3 expression after sciatic nerve injury. Method: Thirty male Wistar rats aged 3 months were divided into sham operated and crush injury group. Termination was performing at days 3, 7 and 14. Lumbar spinal cord segments 4-5 (VTh12-VL1 high) embedded in paraffin blocks. Imunohistochemistry staining was performed using antibody of SIRT1 nuclear marker and activated Caspase 3. Observations were performed by two double blinded observers in 400x magnification. The data were analyzed using unpaired t-test and Pearson correlation. All data were processed using statistical analysis with confidence interval (CI) 95% and limit of significance (p-values)<0.05. Results: SIRT1 expression on the anterior horn was higher compared with control at days 7 and 14 (p<0.05), but no differences were found on posterior horn at all termination days(p>0.05). Activated Caspase 3 expression on the anterior horn was higher at all termination days(p<0.05) and at day 7 on posterior horn (p<0.05). Thereis a positive correlation between SIRT1 and activated Caspase 3 expression on anterior horn at day 7 (p<0.05). Conclusion: SIRT1 expression on the anterior horn was higher compared with the control at days 7 and 14. Activated Caspase 3 expression on the anterior horn was higher on all termination days and at day 7 on posterior horn. There is a positive correlation between SIRT1 and activated Caspase 3 expression on anterior horn on day 7. Bangladesh Journal of Medical Science Vol.18(1) 2019 p.50-56